2018
DOI: 10.1182/blood-2018-05-848473
|View full text |Cite
|
Sign up to set email alerts
|

Mutational landscape of myelodysplastic/myeloproliferative neoplasm–unclassifiable

Abstract: F, et al. New comprehensive cytogenetic scoring system for primary myelodysplastic syndromes (MDS) and oligoblastic acute myeloid leukemia after MDS derived from an international database merge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…De-Morgan et al studied the genomic data of 2773 MDS patients and showed that men have higher incidence of U2AF1 and ZSRS2 mutations whereas women with MDS have higher incidence of DNMT3A and TP53 mutations [ 8 ]. Bose et al, performed an analysis of the genomic landscape of 102 patients with unclassifiable MDS/MPN syndrome and further confirmed that women have a higher incidence of DNMT3A mutations while mutations in the ASXL1 gene were more common among men [ 31 ]. We recently studied the mutational landscape of 100 patients with MDS/MPN and found that men have a higher number of somatic mutations and higher frequency of mutations in the EZH2 gene independent of the specific disease sub-type (Karantanos et al, under review).…”
Section: Sex-related Differences In the Genomic Profile Of Patientmentioning
confidence: 99%
“…De-Morgan et al studied the genomic data of 2773 MDS patients and showed that men have higher incidence of U2AF1 and ZSRS2 mutations whereas women with MDS have higher incidence of DNMT3A and TP53 mutations [ 8 ]. Bose et al, performed an analysis of the genomic landscape of 102 patients with unclassifiable MDS/MPN syndrome and further confirmed that women have a higher incidence of DNMT3A mutations while mutations in the ASXL1 gene were more common among men [ 31 ]. We recently studied the mutational landscape of 100 patients with MDS/MPN and found that men have a higher number of somatic mutations and higher frequency of mutations in the EZH2 gene independent of the specific disease sub-type (Karantanos et al, under review).…”
Section: Sex-related Differences In the Genomic Profile Of Patientmentioning
confidence: 99%
“…The International Prognostic Scoring System–Revised (IPSS-R) developed for MDS combined with cytogenetics is often used in clinical practice and studies, but its prognostic usefulness has been uncertain. 12 14 In contrast, Mangaonkar et al 11 found that both IPSS-R and Global MD Anderson (MDA) model successfully risk stratified 135 MDS/MPN-U patients at 3 years follow-up. Palomo et al 5 found that the presence of cytogenetic abnormalities was associated with an inferior overall survival (OS) in MDS/MPN neoplasms, except for aCML.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 17 In Table 3 , we have summarized the current knowledge regarding their prevalence and potential prognostic value in different myeloid malignancies. 5 , 7 , 12 , 16 , 19 23 However, due to the rarity of these disease entities and the low prevalence of some of the mutations, their prognostic values are uncertain. Future studies will enhance our knowledge in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Whole genome and whole exome sequencing of hematologic malignancies (78)(79)(80)(81)(82)(83)(84)(85) has revealed the spectrum of fusions and mutations (also referred to as the mutanome) of these diseases, including events that range from rare to highly recurrent. Many of these genetic abnormalities may give rise to neoantigens.…”
Section: Shared Vs Personal Neoantigensmentioning
confidence: 99%